Akuntabilitas Pengelolaan Dana Desa di Kecamatan Kotamobagu Selatan Kota Kotamobagu - Makalalag, Astri Juainita; Nangoi, Grace B; Karamoy, Herman (Universitas Sam Ratulangi, 2017)
Abstract. Village fund management requires the existence of good governance in which one of its pillars is accountability. The allocation of substantial funds is expected to give a significant impact on the welfare of rural communities and also can be reported and accounted for. Management of village fund should be done based on the principle of governance which are transparent, accountable and participatory. This research was conducted in six villages in the South Kotamobagu Districts of Kotamobagu city. 21 respondents were interviewed. They are the fund manager of the village and the village fund facilitator team. This study is a qualitative exploratory research. Data were analyzed by content analysis and technical analysis was the reduction, data presentation and conclusion. The results of this study indicate that the accountability of the village fund management in South Kotamobagu District in Kotamobagu city have been carried out and fulfilled in terms of Â transparency, accountability and participatory. Altough there were several omissions that still be conducted the by village officers and technical executors. In overall, the reporting and accountability have been implemented in accordance with the mechanism of provisions. Competency of management resources are still a major problem requiring the assistance of local government. To improve the accountability in the management of village funds; a sustainable coaching, training, supervision and evaluation to village authorities are needed. Keywords: village fund management, accountability, transparency, participatory. Abstrak. Dalam pengelolaan dana desa dituntut adanya suatu aspek tata pemerintahan yang baik (good governance) dimana salah satu pilarnya adalah akuntabilitas. Alokasi dana yang cukup besar diharapkan dapat memberikan dampak yang signifikan terhadap kesejahteraan masyarakat desa, dan benar-benar dapat dilaporkan serta dipertanggungjawabkan. Pengelolaan keuangan desa dilakukan berdasarkan prinsip tata kelola yaitu transparan, akuntabel dan partisipatif. Penelitian ini dilaksanakan di 6 (enam) desa dalam wilayah Kecamatan Kotamobagu Selatan Kota kotamobagu. Dengan jumlah informan 21 (dua puluh satu) orang yaitu pengelola dana desa dan tim fasilitasi dana desa. Penelitian ini menggunakan metode kualitatif eksploratif. Metode yang digunakan adalah analisis isi dan teknis analisis yang digunakan adalah reduksi, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa akuntabilitas pengelolan dana desa di Kecamatan Kotamobagu Selatan Kota Kotamobagu telah dilaksanakan berdasarkan prinsip transparan, akuntabel dan partisipatif. Dalam pelaporan dan pertanggungjawaban sudah dilaksanakan sesuai dengan mekanisme berdasarkan ketentuan walaupun masih terdapat kelalaian dari aparat desa dan pengelola teknis kegiatan. Kompetensi sumber daya pengelola masih merupakan kendala utama, sehingga masih perlu pendampingan pemerintah daerah. Untuk meningkatkan akuntabilitas dalam pengelolaan dana desa di Kecamatan Kotamobagu Selatan Kota Kotamobagu dibutuhkan pembinaan, pelatihan, pengawasan dan evaluasi secara berkelanjutan kepada aparat desa. Kata Kunci : pengelolaan dana desa, akuntabilitas, transparansi, partisipatif.